2000
DOI: 10.1002/1521-4095(200012)12:23<1801::aid-adma1801>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation into the Origins of Lewis Acidity in Zeolites

Abstract: The catalytic abilities of zeolites are attributed largely to their acidic properties, in both the Brønsted (proton donating) and Lewis (electron accepting) senses, although the origin and mechanism of the Lewis acidity remain unclear. Here is presented a computational approach to identifying Lewis acid sites in zeolite frameworks by analyzing the major candidate structures, such as the Al hydroperoxide shown in the Figure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The activation barriers, however, appeared to be prohibitive (close to 200 kJ/mol) due to a very unstable vicinal disilanol species, where two pentahedral silicon atoms are part of a two-membered ring. Similar disilanol intermediates were previously invoked as possible defects in siliceous zeolite models, [232][233][234] and were also invoked for the desilication of SAPO-34. 240 Silaghi et al identified much easier initiation steps for the dealumination mechanisms upon water attack, 223,241 leading to the formation of a Al(OH) 3 (H 2 O) EFAl, and a silanol nest (Figure 5-b and 4-c).…”
Section: Simulation Of the Dealumination / Desilication Mechanismssupporting
confidence: 60%
“…The activation barriers, however, appeared to be prohibitive (close to 200 kJ/mol) due to a very unstable vicinal disilanol species, where two pentahedral silicon atoms are part of a two-membered ring. Similar disilanol intermediates were previously invoked as possible defects in siliceous zeolite models, [232][233][234] and were also invoked for the desilication of SAPO-34. 240 Silaghi et al identified much easier initiation steps for the dealumination mechanisms upon water attack, 223,241 leading to the formation of a Al(OH) 3 (H 2 O) EFAl, and a silanol nest (Figure 5-b and 4-c).…”
Section: Simulation Of the Dealumination / Desilication Mechanismssupporting
confidence: 60%
“…On the basis of 1 H DQ-MAS NMR and the 13 C MAS NMR of adsorbed 2-13 C-acetone, we have obtained the spatial details of the Brønsted and Lewis acid sites in a dealuminated H-Y zeolite and demonstrated that spatial proximities can result in a synergy effect that remarkably increases the acid strength of the zeolite [27,28]. In zeolites, Brønsted acid sites are due to bridging hydroxyl groups (SiOHAl) and a 4-coordinate framework aluminum, while Lewis acid sites are due to either EFAL [29,30] or three-coordinate framework aluminum species [31,32]. Recently, we have used 27 Al DQ-MAS NMR spectroscopy to reveal the detailed spatial proximities of the various aluminum species in dealuminated H-Y zeolites [33].…”
Section: English Textmentioning
confidence: 99%
“…5 Experimental evidence for a catalytic activity of Lewis sites can be found, e.g., in the work of Wichterlová et al 5 Investigation of possible defect sites created by thermal treatment is therefore necessary to improve our understanding of the catalytic properties of zeolites. Sokol et al 6 have discussed the formation of the defects in sodalite and chabazite structures; however, only bulk structures have been taken into account.…”
Section: Introductionmentioning
confidence: 99%